Determining the Relationship between Media Literacy and Social Skills - Akti, Seda; Gurol, Aysun (ELSEVIER SCIENCE BV, 2012)
In this study, determining the relationship between media literacy and social skill levels of the eighth grade primary school students, considering various variables, is aimed. With this design, the questions of whether the relationship between media literacy and social skill levels of the eighth grade primary school students differs significantly according to gender, having access to internet; as well as whether there is a relationship between media literacy and social skill levels are tried to be answered. This study is based on correlative survey model among general survey models. The study group consists of 947 eighth grade primary school students who study at the schools selected randomly from five different educational areas in the city center of Elazig. Economical conditions and family profiles were considered in selection of those schools. In the study, two different assessment scales have been used to receive students' opinions. One of them is the Level Determination Scale for Media Literacy which was developed by Karaman ve Karatas (2009) and the other one is the Social Skill Inventory, as translated into Turkish by Galip Yuksel in 2004, which was developed by Riggio in 1989. The study has showed that there is not a significant relationship between media literacy level and social skill level. Considering the relationship according to the sub-factors, it is observed that there is a relationship between some sub-factors; however this relationship is very weak. It is observed that gender of the students does not form a significant difference for media literacy but it does for social skill level. Furthermore, female students' social skill levels are found to be higher. It is observed that the school which the students attend affects neither media literacy nor social skill levels. (C) 2012 Published by Elsevier Ltd. Selection and/or peer-review under responsibility of The Association Science Education and Technology
Keywords: Media Literacy; Social Skill; Social Development; Primary Education; Computer Science; Education & Educational Research